An efficient approach for binary classification in brain tumor detection using convolutional neural network - Islam, MD. Arman; Noshin, Sheikh Araf; Islam, MD. Robiul; Razy, MD. Farhan; Antara, Samiha (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.